2017
DOI: 10.1038/s41598-017-09259-1
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of cytotoxic natural killer cells using irradiated autologous peripheral blood mononuclear cells and anti-CD16 antibody

Abstract: Natural killer (NK) cells are considered a promising strategy for cancer treatment. Various methods for large-scale NK cell expansion have been developed, but they should guarantee that no viable cells are mixed with the expanded NK cells because most methods involve cancer cells or genetically modified cells as feeder cells. We used an anti-CD16 monoclonal antibody (mAb) and irradiated autologous peripheral blood mononuclear cells (PBMCs) (IrAPs) to provide a suitable environment (activating receptor-ligand i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 61 publications
(72 reference statements)
1
39
0
Order By: Relevance
“…68 In vivo experiments immunising C57BL/ 6 mice with irradiated B16-F-10 melanoma (15 Gy) showed a significant accumulation of CD3 À NK1.1 + NK cells with a substantial increase in the immune regulatory NK cell subpopulation CD27 + CD11b À . 69 Another study led by Lee et al 70 examining cytotoxic NK cell expansion demonstrated that 25 Gy radiation induced upregulation of costimulatory receptors (NKG2D) critical for NK cell activation. In this study, low-dose radiotherapy of 75 mGy (12.5 mGy min À1 ) increased NK cell infiltration and induced strong cytotoxicity compared to sham irradiation.…”
Section: Increasing Natural Killer Cytotoxicitymentioning
confidence: 99%
“…68 In vivo experiments immunising C57BL/ 6 mice with irradiated B16-F-10 melanoma (15 Gy) showed a significant accumulation of CD3 À NK1.1 + NK cells with a substantial increase in the immune regulatory NK cell subpopulation CD27 + CD11b À . 69 Another study led by Lee et al 70 examining cytotoxic NK cell expansion demonstrated that 25 Gy radiation induced upregulation of costimulatory receptors (NKG2D) critical for NK cell activation. In this study, low-dose radiotherapy of 75 mGy (12.5 mGy min À1 ) increased NK cell infiltration and induced strong cytotoxicity compared to sham irradiation.…”
Section: Increasing Natural Killer Cytotoxicitymentioning
confidence: 99%
“…Lee et al [92] successfully amplified a large number of the cytotoxic natural killer cells by the use of radiation irradiation of autologous peripheral blood mononuclear cells and induction of anti-CD16 monoclonal antibody. It was found that this method could effectively amplify NK cells and obtain high purity and activating NK cells with less T cell contamination.…”
Section: Nkg2d Signaling Induces High Expression Of Cd16 On Nk Cellsmentioning
confidence: 99%
“…One of the problem solving approaches is transplantation of NK cells to HCC patients, but the amount of NK cells derived from various sources is less than clinical use. Therefore, many techniques have been proposed for activation and expansion of NK cells (Cho and Campana, 2009;Ahn et al, 2013;Kamiya et al, 2016;Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In some methods, it is suggested to expansion of NK cell from whole peripheral blood lymphocytes after inhibition of T cells proliferation but some T cells may be remain after NK cell expansion (Alici et al, 2008;Fujisaki et al, 2009;Klingemann and Martinson, 2004;Peng et al, 2004). Therefore, some studies used irradiated autologous PBMC with the cytokines and mABs, as feeder layer, for NK cell expansion (Ahn et al, 2013;Lee et al, 2017). Many cytokines, have been applied for expansion and activation of NK cells such as IL-21, -18, -15, -12 and -2(Cooper et al, 2009;Romee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%